Why random finite sets? - Mullane, J.; Vo, Ba-Ngu; Adams, M.; Vo, B. (2011)
We begin the justification for the use of RFSs by re-evaluating the basic issues of feature representation, and considering the fundamental mathematical relationship between environmental feature representations, and robot motion. We further the justification for the use of RFSs in FBRM and SLAM by considering an issue of fundamental mathematical importance in any estimation problem - estimation error.